Purification and Partial Characterization of Bacteriocin Lac-B23, a Novel Bacteriocin Production by Lactobacillus plantarum J23, Isolated From Chinese Traditional Fermented Milk - Zhang, Jianming; Yang, Yanyan; Yang, Hui; Bu, Yushan; Yi, Huaxi; Zhang, Lanwei; Han, Xue; Ai, Lianzhong (Frontiers in Microbiology, 2018)
The exploration and evaluation of bacteriocin-producing lactic acid bacteria (LAB) have been one of the powerful means to food preservation. A total of 300 strains were isolated from Chinese traditional fermented milk products. A bacteriocin-producing LAB, named Lactobacillus plantarum J23, was screened and identified. Bacteriocin Lac-B23 from L. plantarum J23 was purified by 80% ammonium sulfate precipitation, cation-exchange chromatography, and reverse-phase high-performance liquid chromatography. Molecular weight of bacteriocin Lac-B23 was determined to be approximately 6.73 kDa by tricine sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis, and it was confirmed as a novel bacteriocin by liquid chromatography-mass spectrometry. Moreover, bacteriocin Lac-B23 showed thermal stability when heated at below 100°C for 30 min, pH stability between pH 2.0 and 12.0, and sensitivity to trypsin, proteinase K, and proteinase E. The antimicrobial activity of bacteriocin could be enhanced by addition of Fe2+, Mn2+, and ethyl alcohol, and inhibited by Cu2+, K+, Ca2+, Zn2+, Mg2+, and sodium chloride. The results suggested bacteriocin Lac-B23 to have potential application prospects in the food industry.